Difficulties experienced by a group of nursing students during pandemic process and their coping strategies: A qualitative research - KARACA, SEMRA; KARAKOÇ, AYŞE (My University, 2022)
Objective: This phenomenologic study aims to investigate the difficulties experienced by a group of nursing students during the pandemia process thoroughly and to explain coping strategies. Methods: This research was carried out using the phenomenological method, which is one of the qualitative research methods, to examine the views of nursing students on their pandemic experiences and their coping strategies “Information Form” and “Questionnaire Form” were sent to the students online, and forms that were filled out completely and sent back were included in the content analysis. Results: Participants mean age was 21.19±1.06. Of the participants, 77.00% were female, 34.4% stated that they live in a metropolis during the pandemia process, while 83.6% mentioned that they were with their family, 31.1% did not leave their homes unless it is necessary. As a result of data analysis, the main themes of difficulties/stressors, stress/anxiety increasing factors, and coping strategies were reached. Conclusion: Student nurses experience more than one difficulty regarding the pandemia process; some students state that the pandemia process has changed their perception of their profession, and they mostly use positive methods to cope with these difficulties.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Reviews and References (medical); Research and Theory; Pandemic; difficulties; coping; nursing students; HEALTH-CARE WORKERS; STRESS; Pandemic; difficulties; coping; nursing students